PENERAPAN PASAL 2 AYAT 1 UNDANG-UNDANG SENJATA TAJAM DALAM PENUNTUTAN TERHADAP TINDAK PIDANA PENGANIAYAAN MENGGUNAKAN SENJATA TAJAM DALAM PERKARA KEJAKSAAAN KOTA SUKABUMI - Aulia Puspita; Haidan Angga Kusumah (JOURNAL OF LAW AND NATION, 2024)
Maltreatment is a form of violence that physically or mentally injures the victim. The method used in the research is descriptive method with qualitative approach through field research. This study aims to determine the considerations of the public prosecutor in determining the charges for the crime of persecution using sharp weapons and to determine the implications of the public prosecutor's considerations in prosecuting the crime of persecution using sharp weapons in the Sukabumi City Prosecutor's Office case No. PDM-42/SKBMI/Euh.1/09/2021. The type of legal research conducted is normative juridical, namely legal research conducted based on primary legal materials by examining theories, concepts, legal principles and laws and regulations related to this research. This research was conducted in Sukabumi City Prosecutor's Office and Sukabumi District Prosecutor's Office. Data collection techniques in this research are observation, interview, documentation and literature study. The results showed that in determining criminal charges, public prosecutors used the dominus litis principle and the principle of public prosecutors to prosecute crimes and research showed that although there were differences in views between public prosecutors in criminal trials, the differences ultimately determined the judge to impose a verdict.